A convective heated digestion system with closed vessels: a new digestor for elemental inorganic analysis - Vieira, Alan Lima; Arantes de Carvalho, Gabriel Gustinelli; Gomes Neto, José Anchieta [UNESP]; Oliveira, Pedro Vitoriano; Kamogawa, Marcos Yassuo; Virgilio, Alex (Royal Society of Chemistry (RSC), 2023)
This work presents a new, robust, and reliable conductively heated digestion system with closed vessels (CHDS) for the preparation of plant materials for elemental determination by inductively coupled plasma optical emission spectrometry (ICP OES). The proposed system combines the simplicity of a 24-slot resistively heated aluminum block with the key advantages inherent to closed vessels. Fundamental studies on temperature and pressure were also performed and the difference between the liquid phase temperature (190 °C) and the aluminum block temperature (240 °C) was assigned to the dynamic condensation of the gaseous phase during digestion. The optimized digestion procedure was achieved for 250 mg test portions, 2.0 mL of HNO3 (65% v v−1), 1.5 mL of H2O2 (30% v v−1), and a temperature of 240 °C, with a heating rate of 10 °C min−1 and dwell time of 20 min. Under these conditions, the residual carbon contents in digests were generally below 700 mg L−1. The performance of the CHDS was checked by analyzing plant certified reference materials and the determined concentrations of B, Ca, Cu, Fe, K, Mg, Mn, P, S, and Zn presented no significant differences when compared to the certified values at the 95% confidence level. Recoveries in the 75-108% range and relative standard deviations ≤3% (n = 3) were typically obtained. Also, the system was applied to the analysis of sixteen samples from an interlaboratory trial, and a comparison with alternative single reaction chamber microwave-assisted digestion (SRC MWAD) and open vessel nitro-perchloric decomposition (NP) digestion methods also showed equivalence at a 95% confidence level in most cases. The CHDS system based on thermally convective heating allowed digestion of up to 24 different plant materials in ca. 50 min, but it is not limited to samples and analytes chosen in this work: the CHDS is designed for typical use in elemental inorganic analysis techniques that require liquid-based sample introduction.